2004
DOI: 10.1097/00126334-200404150-00010
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Impact, Acceptability, and HIV Incidence Among Homosexual Men With Access to Postexposure Chemoprophylaxis for HIV

Abstract: PEP was safe and did not appear to be associated with increases in reported high-risk behavior in our cohort. Ready access to PEP did not appear to substantially affect HIV transmission, suggesting a limited public health impact of this intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
156
2
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(173 citation statements)
references
References 17 publications
8
156
2
7
Order By: Relevance
“…Likewise, in Spain, among people who looked for the anti-HIV test, 22% of them knew PEPsexual, and 2% had used this technique 89 . The use of the method was also low (34%) among homosexuals who received ART to start prophylaxis in case of an unprotected relation 90 . Some of the reasons for low use are individual characteristics (i.e., perception of no risk and fear of adverse events); health services (i.e., few places that offer the medicine and time of service); and the method itself (i.e., 72-hour limit for the beginning of prophylaxis).…”
Section: The Last Option Of Prevention For Non-infected People: Post-mentioning
confidence: 99%
“…Likewise, in Spain, among people who looked for the anti-HIV test, 22% of them knew PEPsexual, and 2% had used this technique 89 . The use of the method was also low (34%) among homosexuals who received ART to start prophylaxis in case of an unprotected relation 90 . Some of the reasons for low use are individual characteristics (i.e., perception of no risk and fear of adverse events); health services (i.e., few places that offer the medicine and time of service); and the method itself (i.e., 72-hour limit for the beginning of prophylaxis).…”
Section: The Last Option Of Prevention For Non-infected People: Post-mentioning
confidence: 99%
“…Most PEP regimens consist of taking one to three different types of antiretroviral drugs for up to a period of two weeks. While the use of PEP is typically considered a last resort to avert an HIV infection, there is evidence that high risk individuals are more likely to rely on using PEP and that PEP could inadvertently increase an individual's sexual risk behavior [30].…”
Section: Post Exposure Prophylaxis (Pep)mentioning
confidence: 99%
“…Seroincidence was 0.7 per 100 person-years (one seroconversion) among men who took nPEP and 4.1 per 100 person-years among men who did not take nPEP (11 seroconversions) (22,23). Subsequent analysis of data from patients who took nPEP and had been followed for a median of 24.2 months indicated 11 seroconversions and a seroincidence of 2.9 per 100 person-years, compared with an expected seroincidence of 3.1 per 100 person years, p>0.97) (24). In a study of sexual assault survivors in Sao Paolo, Brazil, women who sought care within 72 hours after exposure were treated for 28 days with either zidovudine and lamivudine (for those without mucosal trauma) or zidovudine, lamivudine, and indinavir (for those with mucosal trauma or those subjected to unprotected anal sex) for 28 days.…”
Section: Observational Studies Of Npepmentioning
confidence: 97%
“…A similar proportion of participants (14%) requested a second course of nPEP at the Fenway Clinic in Boston (31). In the Brazil nPEP study of homosexual and bisexual men followed up for a median of 24 months, all groups, including those who elected to take nPEP, reported decreases in risk behavior (24,32). Among highly educated (75% with >4 years of college), predominantly white (74%) homosexual men who completed a street-outreach intervieweradministered survey in San Francisco, those who reported that they were aware of the availability of nPEP did not report more risk behavior than those who were not aware (33).…”
Section: Effects On Risk-reduction Behaviorsmentioning
confidence: 99%